Volatile profile of Arbutus unedo L. fruit through ripening stage - Oliveira, Ivo (2014)
Arbutus unedo L. is a Mediterranean shrub used in the production of jams, marmalades and beverages, as well as in traditional medicine. In this work, the effect of ripening on the volatile compounds of the fruits of A. unedo was evaluated, using headspace-solid phase microextraction combined with gas chromatography/ ion trap-mass spectrometry. Alcohols are the main component of the volatile fraction of A. unedo fruits, followed by aldehydes and esters. The main volatile compounds identified were (Z)-3-hexen-1-ol, 1-hexanol, hexanal, (E)-2-hexenal and hexyl acetate, all formed through the lipoxygenase pathway (LOX). The green odours are progressively replaced during ripening by floral and sweet sensations, due to the decrease in alcohols, aldehydes and esters, resulting in the unmasking of the aromas associated with the minor compounds (mainly monoterpenes and norisoprenoid compounds) that compose A. unedo fruits.